Pengaruh Intervensi Makanan Tambahan Padat Energi dan Protein Berbasis Pangan Lokal terhadap Perbaikan Status Gizi Balita - Utma Aspatria (Universitas Nusa Cendana, 2020)
Malnutrition problems that mostly occur in NTT are particularly caused by low protein intake. Therefore, this study was designed to intervene in feeding energy and protein dense snack to improve the nutritional status of children under five. This research was conducted in Tanah Putih Village, Kupang Tengah Sub-district, Kupang District. The research was an experimental method with a completely randomized design. Three types of intervention were given, namely: p1 = cassava + skipjack fish; p2 = cassava + rice beans; and p3 = cassava + skipjack fish + rice beans. Each sample consumed energy and protein dense snacks (according to treatment) for 30 days of trial. The results showed that the majority of children had a higher acceptance level for the intervention (88,9%). The results also showed that the provision of energy-dense food and protein significantly (p <0.05) improved the nutritional status of children under five, with weight for height indicator. However, the intervention had no significant effect (p> 0.05) with the indicator of height for age. The results of the analysis of variance showed a significant nutritional status improvement for the composition of cassava and fish (P1) (p <0.05) using the indicators wight for height and weight for age. Yet, it had not significantly contributed to improving the nutritional status of children under five using the height for age indicator.Advanced analysis using the Duncan test showed that the intervention treatment with the composition of cassava and rice beans had the strongest effect on improving the nutritional status of children under five.